Build real world websites from scratch using HTML5 and CSS3 (Packt Publishing, 2018)
"This an engaging course, that makes your learning experience fun and exciting while you are acquiring precious skills that will prepare you to become one of the most sought after professionals in the web development market. First of all, you are going to understand the structure of a web page. Then you will setup your free web hosting which comes as a bonus with this course. After that, you will move to HTML5 and learn the components that build up the skeleton of a web page; you will cover various concepts to a detailed level: paragraph, links, forms, iframes, and so on. Then, you will move to CSS3 and learn how to add professional decoration and styling to your websites, you will also be introduced to advanced skills like CSS3 transitions and animations."--Resource description page